An EVP Double-Yield Nonstationary Flow Surface Model for Soft Clay - Liucheng Chang; Hongyu Wang; Ya Wang (Advances in Civil Engineering)
According to experimental findings, soft clay has compression and shear creep. The goal of the study is to develop an elastic-viscoplastic (EVP) model for the viscous behavior of soft clay. The new EVP model is deduced from the associated flow rule, Yin’s double-yield surface theory, and the critical state soil mechanics. The nonstationary flow surface model with double-yield surface, compared to other existing models, considers the compression and shear creep properties of soft clay. The model parameters can be identified from two sorts of tests (i.e., the general triaxial tests and triaxial rheological tests). Different types of soft clay, such as Tianjin Coastal clay, Shantou dredger fill, and silted soil in front of dam, were tested to verify the accuracy of the constructed model. All comparisons of computed and experimental findings revealed that the new EVP model accurately reflected the time-dependent behaviors of soft clay in both shear and compression creep.